PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI STRUKTUR ATOM DI KELAS X SMA NEGERI 11 KOTA TERNATE - Sisilia Taliawo; Zulkifli Zam Zam; St Hayatun Nur Abu (EDUKASI, 2020)
This research was conducted to determine the increasing learning model of snowball throwing in students learning achievement on the subject matter of atomic structure in grade X of SMAN 11 Kota Ternate amounting to 15 students. The sample of this research was students grade X that was taken by saturated sampling. The instrument used in this research is essay consist of 9 items to use for quantifying students learning achievement. The technique of data analysis through inferential statistics analysis by using spss 21. The result shows that there are improvements in students learning achievement in grade X of SMAN 11 Kota Ternate on the subject matter of atomic structure based on the hypotheses by t count ˃ t table or 14,140 ˃ 2,144. The gain value was 0,30 shows the was on interpretation of students learning achievement.